Agricultural Wastes as Adsorbents for the Removal of Toxic Metal Ions from Industrial Effluents - Singh, Joginder (My University, 2013)
Millions of people worldwide are suffering with the scarcity of fresh and clean drinking water, which is a fundamental need for all human beings. Freshwater resources are continuously degrading mainly due to the hasty pace of unplanned urbanization, industrialization, population growth, over exploitation and poor management. The main sources of freshwater pollution can be attributed to discharge of untreated sanitary and toxic industrial wastes, dumping of industrial effluent and runoff from agricultural fields. It is well known that 70-80% of diseases in developing countries are due to the consumption of contaminated water. Metal ions are one of the main categories of water pollutants as they are toxic for humans when penetrated the foodchain pyramid. Various toxic heavy metals (Chromium, Nickel, Copper, Zinc, Lead, Cadmium, Mercury, Arsenic, Molybdenum, Cobalt and Uranium) discharged into the environment through different industrial activities are the major causes of water pollution. These metals are highly toxic and it is compulsory to treat the industrial wastewater to permissible limits before disposal into normal water bodies. Several treatment technologies such as membrane processes, ion exchange, precipitation and coagulation have been applied in past to remove heavy metal ions from industrial wastewater. However, these methods posses various disadvantages such as lack of cost effectiveness, production of toxic chemical sludge etc. Therefore the removal of toxic heavy metals from industrial effluents in a cost effective and environment friendly manner is of greater significance. Biosorption of metal ions by agricultural residues seems to be an ecofriendly technology to clean up contaminated water. In this context, present work envisaged to prepare, characterize and evaluate the metal uptake capacity of the agricultural residues from synthetic and industrial wastewater. Mainly four different biosorbents viz., Arachis hypogea shell powder, Trifolium alexandrinum biomass powder, Eucalyptus sp. saw dust and Citrus limetta peel powder have been prepared and employed for the water treatment. Arachis hypogea shell powder used was activated using different concentration of hydrochloric acid and in one of the experiment, the fungus Aspergillus niger was employed on Citrus limetta peel powder for decomposing it and the decomposed, dead biomass was employed for biosorption purposes. The influence of pH, initial metal ion concentration, adsorbent dose, and contact time were studied and the experimental data obtained were evaluated and fitted using equilibrium isotherms and kinetic models. FTIR analyses of the biosorbents were done to study the functional groups involved in metal binding. SEM-EDX was employed to study the surface morphology and to analyze the biosorbed metal ions. Mechanistic aspect of metal biosorption were investigated via chemical blocking of the functional groups and the release of alkali and alkaline earth metals during biosorption of the metal ions. This study supported that ion-exchange mechanism is involved in metal biosorption. Under optimized conditions for different metal ions, column studies were conducted in both down flow and up flow mode using the electroplating, lead acid battery and paint manufacturing industrial wastewater. The column breakthrough curves were analyzed at different flow rates and bed depths, and best fittings were obtained by following the Thomas and BDST models. To demonstrate the reusability of the biosorbents, they have been regenerated by different desorption agents viz., HCl, H2SO4 , HNO3, NaOH and EDTA. Thus, it could be concluded from the present work that biosorbents prepared from agricultural wastes have excellent potential for the removal of Cr(VI), Cu2+, Ni2+, Zn2+, Pb2+ and Cd2+ from different industrial effluents with high biosorption capacity.
PHD, SCBC
Keywords: Agricultural residue; chemical blocking; Up flow column studies